2013
DOI: 10.1039/c2cc37271a
|View full text |Cite
|
Sign up to set email alerts
|

Design of irreversible optical nanothermometers for thermal ablations

Abstract: Nanothermometers composed from a gold nanorod core, temperature sensitive linker and fluorescent dye are reported. The nanothermometers have low fluorescence due to a self-quenching mechanism at temperature below 50°C and become highly fluorescence above 70°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 27 publications
(26 reference statements)
0
40
0
Order By: Relevance
“…32 bBSA is known to bind to both glass and Au surfaces; on glass, through non-covalent physisorption, while on Au surfaces, through coordinative interaction between gold and the bBSA thiol groups. [54][55][56] When AuNS substrates were coated with bBSA monolayers, their LSPR peak positions were red-shifted by about 6-9 nm, due to the higher refractive index of bBSA compared to air ( Figure S4, Supporting Information). Similarly, a previous report showed bBSA provides a spacing of ~4-8 nm between the dye molecules and the Au surface, while the streptavidin attached to the dyes, provides an additional separation distance of ~4 nm, resulting to a total spacing of ~12 nm.…”
Section: 61mentioning
confidence: 99%
See 1 more Smart Citation
“…32 bBSA is known to bind to both glass and Au surfaces; on glass, through non-covalent physisorption, while on Au surfaces, through coordinative interaction between gold and the bBSA thiol groups. [54][55][56] When AuNS substrates were coated with bBSA monolayers, their LSPR peak positions were red-shifted by about 6-9 nm, due to the higher refractive index of bBSA compared to air ( Figure S4, Supporting Information). Similarly, a previous report showed bBSA provides a spacing of ~4-8 nm between the dye molecules and the Au surface, while the streptavidin attached to the dyes, provides an additional separation distance of ~4 nm, resulting to a total spacing of ~12 nm.…”
Section: 61mentioning
confidence: 99%
“…[54][55][56] SEM imaging showed that the surfaces of substrates fabricated with S-AuNS (Figure 3a) and L-AuNS ( Figure 3d) were densely populated by particles. SAuNS were more homogeneously distributed on the surface of glass substrates compared to L-AuNS, possibly due to an increased propensity of L-AuNS to aggregate in solution before self-assembly.…”
Section: Synthesis Of Self-assembled Monolayers Of Auns Grafted On Glmentioning
confidence: 99%
“…Gemcitabine interferes with DNA synthesis following phosphorylation by deoxycytidine kinase and hence is used as a first-line therapy for pancreatic cancer treatment (Gustafson et al 2013). However, rapid development of resistance limits its application.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…11 Recently, we approached this problem by developing nanothermometers composed from a gold nanorod core, temperature sensitive linker, and fluorescent dye. 12 The nanothermometers demonstrated low fluorescence due to a self-quenching mechanism at temperature below 50 ºC and became highly fluorescent above 70 ºC.…”
Section: Introductionmentioning
confidence: 99%